Multilocation Test Of Mutants (M4) Local Red Rice Sigah In Maninjau And Padang - Irfan Suliansyah; Yusniwati Yusniwati; Fadilla Arishadea (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
The 3rd generation mutant brown rice from the experimental cultivation of the 3rd generation mutant has problems in plant characteristics and various genetic traits. In the results of the research of the 3rd generation of mutants, several mutants with production levels were obtained in accordance with the initial objectives of the study, namely early-mature mutants and significant plant height. However, some mutants have unstable plant characters and traits, so a multi-location test of cultivation of the 3rd generation mutant was carried out at two locations with different elevations in order to obtain a 4th generation mutant which is more stable and has uniform characters and properties. This research was conducted in Jorong Sungai Batang, Tanjung Raya District, Agam Regency with a medium elevation level of 637,032 m above sea level and in Surau Gadang Village, Nanggalo District, Padang City with a minimum elevation level of 10.363 m above sea level. This research was carried out from December 2019 to April 2020. The materials used were M3 harvested red rice seeds of the Sigah genotype, namely mutant numbers MG13, MG9, MG2-209, MG5-58,MG6 and control seeds of red rice genotype Sigah. The purpose of the study was to obtain diversity and determine the stability of agronomic characters in the production of local red rice yields of West Sumatran Sigah M4 variety at two different elevations of the cultivation environment. From the results of the research, it was found that the diversity and agronomic characters of plants were quite stable in mutants numbered MG13, MG2-209 and MG5-58 with early plant age, and stable growth in the generative and vegetative phases.